2021
DOI: 10.1007/s11948-021-00326-5
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Students as Co-creators in an Ethics of Technology Course

Abstract: Research on the effectiveness of case studies in teaching engineering ethics in higher education is underdeveloped. To add to our knowledge, we have systematically compared the outcomes of two case approaches to an undergraduate course on the ethics of technology: a detached approach using real-life cases and a challenge-based learning (CBL) approach with students and stakeholders acting as co-creators (CC). We first developed a practical typology of case-study approaches and subsequently tested an evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 61 publications
(77 reference statements)
0
8
0
1
Order By: Relevance
“…Oral feedback was organized in weekly coaching sessions (van Diggelen et al, 2019) to support students to give meaning to the process they went through. The number of respondents was too small to perform cluster analysis in the way we did in this article, but the analysis showed that a redesign based on the cluster analysis led to results for the entire group that was significantly better for competence, autonomy, and intrinsic motivation compared to the classical approach (G. Bombaerts et al, 2021).…”
Section: Discussionmentioning
confidence: 81%
“…Oral feedback was organized in weekly coaching sessions (van Diggelen et al, 2019) to support students to give meaning to the process they went through. The number of respondents was too small to perform cluster analysis in the way we did in this article, but the analysis showed that a redesign based on the cluster analysis led to results for the entire group that was significantly better for competence, autonomy, and intrinsic motivation compared to the classical approach (G. Bombaerts et al, 2021).…”
Section: Discussionmentioning
confidence: 81%
“…Co-teaching activities involving engineering and philosophy or social sciences instructors can address the problem of expertise and convey to students a message about the importance of this subject. Nevertheless, it is an expensive, time and labour-intensive approach, which requires long-term contact and research efforts (Bombaerts et al, 2021 ). Moreover, this approach is considered “second-rate academic work” (Taebi & Kastenberg, 2019 , p. 1768), and is not properly acknowledged in promotion and hiring schemes (National Academy of Engineering, 2017 , p. 12).…”
Section: Multi-level Analysis Of the Challenges Of Engineering Ethics Educationmentioning
confidence: 99%
“…Nevertheless, despite the variety of teaching methods and the prevalence of case studies, there is limited empirical research that could elucidate the effectiveness of each teaching approach towards the attainment of clearly defined goals, as well as their impact on student engagement (Bagdasarov et al, 2013 ; Bombaerts et al, 2021 ; Martin et al, 2021 ; Thiel et al, 2013 , p. 267). There is also little known on how cases are presented in engineering ethics instruction and the kind of cases used (Yadav et al, 2007 ), how they should be taught (Davis & Yadav, 2014 , p. 172), and what approach serves the achievement of which learning goals (Romkey, 2015 ).…”
Section: Multi-level Analysis Of the Challenges Of Engineering Ethics Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these challenges and encourage engineers to take their responsibilities to heart, engineering programmes need to familiarise students early with the features of a VUCA (Volatile, Uncertain, Complex and Ambiguous) problem, that requires a mix of socio-technical skills. Such ill-structured learning activities [43,45] can offer students a deeper exposure to ethics and enhance their motivation to engage with ethical topics ( [27,28,32,[39][40][41]). They can also contribute to students' awareness of the varied ethical situations they might encounter in their practice or the type of responsibilities they can take on in their profession [29].…”
Section: B Responsibility In the Context Of Challenge Based Learningmentioning
confidence: 99%